DETERMINING AND ANALYZING THE FUNCTIONAL-SEMANTIC FEATURES OF PHARMACEUTICAL NEOLOGISMS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the functional and semantic characteristics of neologisms emerging in the pharmaceutical field. The study focuses on the formation, usage context, and linguistic and social aspects of these new words. Neologisms are classified based on morphological methods, semantic analysis, and stylistic features.